A first‐in‐human, single and multiple dose study of lunsekimig, a novel anti‐TSLP/anti‐IL‐13 NANOBODY® compound, in healthy volunteers - Annemie Deiteren; Lieselot Bontinck; Griet Conickx; Marie Vigan; Nele Dervaux; Matthieu Gassiot; Selcuk Bas; Benjamin Suratt; Heribert Staudinger; Emmanuel Krupka (Wiley, 2024)
Abstract Lunsekimig is a novel, bispecific NANOBODY® molecule that inhibits both thymic stromal lymphopoietin (TSLP) and interleukin (IL)‐13, two key mediators of asthma pathophysiology. In this first‐in‐human study, we evaluated the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and immunogenicity of lunsekimig in healthy adult participants. Participants received single ascending doses (SAD) of lunsekimig (10-400 mg intravenous [IV] or 400 mg subcutaneous [SC]) (SAD part) or multiple ascending doses (MAD part) of lunsekimig (100 or 200 mg, every 2 weeks [Q2W] for three SC doses), or placebo. Overall, 48 participants were randomized 3:1 in the SAD part and 4:1 in the MAD part for lunsekimig or placebo. The primary endpoint was safety and tolerability. The secondary endpoints included PK, antidrug antibodies (ADAs) and total target measurement. Lunsekimig was well tolerated and common treatment‐emergent adverse events were COVID‐19, nasopharyngitis, injection site reactions, and headache. Lunsekimig showed dose‐proportional increases in exposure and linear elimination. Mean t1/2z of lunsekimig was around 10 days across all IV and SC doses of the SAD and MAD parts of the study. Increases in the serum concentration of total TSLP and IL‐13 for lunsekimig versus placebo indicated target engagement. ADA of low titers were detected in four (11.1%) participants who received lunsekimig in the SAD, and seven (43.8%) in the MAD. In conclusion, lunsekimig was well tolerated in healthy participants with a linear PK profile up to single 400 mg IV and SC dose and multiple doses of 100 and 200 mg SC Q2W, with low immunogenicity.